The Influence of Organizational Climate, Work Discipline, and Work Motivation on Employee Performance at The Office Education and Culture Office - Syam, Akbar; Heryati, Yati; Hajjad, Mu’fidatul Nurul (Manunggal Halim Jaya, 2024)
This research design is quantitative research, which has the aim of knowing the organizational climate, work discipline, and work motivation on team member performance by taking research locations at the Office of Education and Culture of West Sulawesi Province. This study aims to find more deeply related to organizational conditions and team member attitudes in dealing with differences between employees, as well as the attitude of team member discipline at work as team member motivation to work as part of motivation. This study uses multiple linear regression analysis methods because it uses three independent variables and one dependent variable; the research tool uses a questionnaire using a sample of 100 respondents using total sampling who have the status of State Civil Apparatus (ASN) at the Office of Education and Culture of West Sulawesi Province. The t-test results in the table show that the t-value of the organizational climate variable (X1) is 4.192 while the t-estimated value is 1.66105 with a significant value of 0.000 <0.05. So that Ha is accepted and Ho is rejected. Work discipline (X2) is 7.544, while the t-estimated value is 1.66105. So it can be seen that t-calculated> t-estimated, so Ha is accepted and Ho is rejected, meaning that the work discipline variable significantly affects the performance of the West Sulawesi Provincial Education and Culture Office employees. Work motivation (X3) amounted to 9.052, while the t-estimated value was 1.66105. So, it can be seen that t-calculated> t-estimated, with a significant value of 0.000 <0.05. So that Ha is accepted and Ho is rejected. The simultaneous test results show that the f-value is 22.934> f-estimated 2.70 with a significant level of 0.000 <0.05, so this regression model can be used for team member performance variables at the West Sulawesi Provincial Education and Culture Office.